1996
DOI: 10.1002/j.1460-2075.1996.tb00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two DNA-binding sites on the globular domain of histone H5.

Abstract: The nature of the complexes of histones H1 and H5 and their globular domains (GH1 and GH5) with DNA suggested two DNA‐binding sites which are likely to be the basis of the preference of H1 and H5 for the nucleosome, compared with free DNA. More recently the X‐ray and NMR structures of GH5 and GH1, respectively, have identified two basic clusters on opposite sides of the domains as candidates for these sites. Removal of the positive charge at either location by mutagenesis impairs or abolishes the ability of GH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
138
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 50 publications
10
138
1
2
Order By: Relevance
“…Molecules A and B of the dimer differ in the conformation of the winged loop. Molecule A has been typically used for modeling 12,16,18,19). The winged loop of molecule A extends away from the molecule because of hydrophobic intermolecular contacts with the wing of another molecule A in the crystal lattice (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecules A and B of the dimer differ in the conformation of the winged loop. Molecule A has been typically used for modeling 12,16,18,19). The winged loop of molecule A extends away from the molecule because of hydrophobic intermolecular contacts with the wing of another molecule A in the crystal lattice (12).…”
Section: Resultsmentioning
confidence: 99%
“…DOT more diverse, but all had the DNA backbone clamped between Lys-40 and Lys-97. Usually only two GH5 DNA-binding sites are discussed (12,19,22): a primary site contributed by helix H3 and Lys-85 and a secondary site containing Lys-40, Arg-42, Lys-52, and Arg-94. These analyses were based on molecule A of the GH5 structure in which the perturbed wing conformation causes the Lys-85 side chain to extend toward helix H3.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have clearly established that the interaction of H1 with chromatin is dynamic and the overall affinity is governed by a set of interactions mediated by the globular domain (49,50) and the positively charged COOH-terminal tail (51,52). The folded globular domain of H1 binds preferentially to crossovers of duplex strands in superhelical DNA (40), contains two binding sites for DNA (49), and protects an additional 20 bp from micrococcal nuclease digestion (6, 41). The highly basic COOHterminal domain of H1 adopts secondary ␣-helical structure upon binding to DNA (51) and has been identified as the primary determinant of H1 binding to chromatin in vitro (51,53) and in vivo (52).…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that HNF3 binding is required for nucleosome positioning over the albumin enhancer (31,32), consistent with the hepatic-specific expression pattern observed for albumin in vivo. HNF3, which structurally resembles linker histone H5 (34), can bind in place of a linker histone molecule to a degenerate HNF3-binding site on the side of a core nucleosome, but lacks the basic amino acids present in linker histones required to mediate compaction of nucleosomal DNA (35). Our in vitro analysis of HNF3 provides the first demonstration that HNF3-directed structural changes functionally mediate derepression of transcription on a chromatin template.…”
Section: Discussionmentioning
confidence: 99%
“…HNF3␣ is of particular interest as it has been shown to position nucleosomes within the enhancer of the liver-specific albumin gene (31,32). A role for HNF3 in organizing chromatin is further supported by the three-dimensional structural similarity of the winged helix conformation to the globular domain of linker histones (33,34); functional conservation of this domain was confirmed by studies demonstrating the nucleosome-binding properties of HNF3 (35). However, the mechanism by which HNF3 transactivates hepatic-specific genes remains unclear.…”
mentioning
confidence: 98%